Feminism (Also) for Men: Souls, Bodies, and the Question of How to Live - Van Zijl, Berno (The Stellenbosch Socratic Journal, 2025)
This article aims to demonstrate how men who feel confused and irrelevant in feminism classes can engage with feminism on two levels: listening to the voices of women, but also seeing feminism as an opportunity to supplement their own (male) perspectives. It discusses Adriana Cavarero’s In Spite of Plato, and points out that she emphasises its relevance for women much stronger than its relevance for men – almost to the point where the latter is completely eclipsed. Cavarero criticises the Western philosophical tradition originating with Plato as propagating a genderised soul–body hierarchy, in which the male = the soul, the female = the body, and the former is centralised while the latter is merely defined in terms of its deviation from the former. She proceeds to reread (marginalised) female characters from male-produced texts in order to carve out space for an embodied female subjectivity. While she discusses embodied wisdom with regards to Penelope (Odysseus’s wife in *The Odyssey*) and thereby women more generally, she does not emphasise the value of embodiment for men. This article emphasises that the bod(il)y can supplement male subjectivity too and can lead towards a more complete philosophical approach: the abstract intellectualism of the tradition Cavarero criticises is impoverished and cannot satisfactorily address an everyday, situated question such as "How should I live?". Hopefully this will make some of those men in feminism classes feel less confused and irrelevant.